Correction: Functional specific roles of FADD: comparative proteomic analyses from knockout cell lines. (2nd April 2019) - Zhuang, Hongqin; Gan, Ziyi; Jiang, Weiwei; Zhang, Xiangyu; Hua, Zi-Chun
Abstract : Correction for 'Functional specific roles of FADD: comparative proteomic analyses from knockout cell lines' by Hongqin Zhuang et al., Mol. BioSyst., 2013, 9, 2063–2078.